Omotenashi Furumai dalam Konsep Pelayanan di Restoran Jimgu Hotel Enowa Yufuin - Sulistyowati, Rani Tri; Kadafi, Muammar; Felayati, Safrina Arifiani (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2025)
This study aims to explore the implementation of furumai, one of the core elements of omotenashi, Japan’s unique hospitality philosophy through an autoethnographic approach. The research focuses on the service practices at Jimgu Restaurant, Enowa Yufuin Hotel, Japan. Data were collected through reflective narratives of the researcher, who had direct experience as an intern, along with supporting documents such as service SOPs, and service behavior observations. The findings reveal that furumai is not merely about visible service actions, but an expression of cultural values such as rei (courtesy), wa (harmony), and kata (ritualized forms). Furumai manifests in subtle attentiveness, anticipation of unspoken needs, and consistent, heartfelt delivery of service. Through autoethnography, the researcher captures the deep cultural meanings embedded in daily service experiences. The study concludes that furumai is a service ethic rooted in empathy, cultural discipline, and professionalism, offering a relational model distinct from the transactional approach common in Western hospitality. This research contributes to a culturally embedded understanding of service quality.